Mahkamah Konstitusi dan Pseudo Judicial Review dalam Perkara Pemilukada - Irfan Nur Rachman (Jurnal Konstitusi, 2015)
Judicial review is the test act against UUD 1945 that is one authority the constitutional court. In testing legislation affairs, the constitutional court could have cancel or material handling charge article / ayat / part of a statute.  But in the legal developments event at the constitutional court, turned in regional head affair how the constitutional court to review (pseudo judicial testing legislation specious) where the constitutional court to do our tests material charge / article ayat / or part of a statute. The research results show that on formil, judicial review the request in the matter of the act of testing and supplication pseudo judicial review in the matter of the results   of the upcoming general election strife is different because be set by two types of laws the event under the authority of the different. However, in the context of judicial review of the verdict, construction and construction of pseudo judicial review similarities and differences will be discussed in the article below.